Management of cardiac electrical storm: a case report - Oresegun, Olajide O.; Adeleke, Kamar T.; Sanusi, Michael O.; Oluwaferanmi, Morenikeji E.; Sogade, Felix O. (International Journal of Advances in Medicine, 2022)
There is a steady increase in the incidence of intra-cardiac device complications in patients with structural heart diseases. Cardiac electrical storm is associated with deleterious clinical and psychological sequelae. Management can be challenging in a resource-poor environment. Old anti-arrhythmic medications can still be effective when conventional ones fail.